Portraits of Children's Autonomy in PAUD Alam Minangkabau - Reni Junita Sari; Nurhafizah Nurhafizah; Yaswinda Yaswinda (Faculty of Teacher Training and Education, Universitas Terbuka, 2019)
This article is motivated by the results of research on how children's autonomy in PAUD Alam Minangkabau. Autonomy is one aspect of human personality that cannot stand alone, this means that autonomy is related to other aspects of personality such as social aspects, emotional aspects, physical and psychological aspects. The purpose of this study is to describe how the autonomy of children in PAUD Alam Minangkabau. Data collection techniques used are the format of observation, interviews, and documentation. Observations focused on children and interviews were conducted with school principals and teachers on how to instill autonomy. From the results of this study, it is illustrated that almost all children have good autonomy where autonomy has been well developed through the collaboration of parents and teachers in the development of children's autonomy. With the existence of such cooperation the development of autonomy can be carried out maximally. Seen when the child can be left by parents at school and do various activities for him without having to be helped by teachers or other adult.DOI: https://doi.org/10.31098/ijeiece.v1i2.31